Renewable Energy in Bangka Belitung Island Province - Wahri Sunanda; Agung Fitrahadi; Irfan Hilmy (Jurnal Inovasi Teknologi, 2023)
Bangka Belitung Island Province, which consists of 7 regencies/cities, has the potential for new renewable energy, both solar, wind, marine and biomass. Energy management policies in the regions have been outlined in regional regulations concerning the 2019-2050 regional general energy plan. It is targeted that in 2025, the energy mix will reach 17.21% and 30.97% in 2050. This article aims to highlight the potential and challenges on development and managing the renewable energy in Bangka Belitung Island Province.